Tailoring the rheology, structural stability and printability of pea protein–κ-carrageenan hydrogels with Tremella fuciformis polysaccharide for 3D food printing - Hafiz Abdul Rasheed; Lei Wu; Abdur Rehman; Tabussam Tufail; Muhammad Waheed Iqbal; Ahsan Hafiz Muhammad; Ming Cai (Journal of Food Engineering, 2027)

Adaptive functional traits and soil characters drive the successful naturalization of Solanum viarum; An alien species in subtropical forest - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal (Journal for Nature Conservation, 2026)

Molecular insights and antibiotic resistance genes characterization in clinical Vibrio cholera isolates from patients in Peshawar, Pakistan - Muhammad Atif; Jawad Ahmad; Aisha Irfan; Hafiza Misbah Ahmad; Aiman Waheed; Khalid Khan; Numan Fazal (Molecular Biology Reports, 2026)

Understanding the heat stress mitigation mechanisms during pollen development in Gossypium hirsutum L. - Rabia Habib; Zulqurnain Khan; Abdel-Halim Ghazy; Shoaib ur Rehman; Kotb A. Attia; Maria Siddique; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Abu Bakar Saddique; Ummara Waheed (Molecular Biology Reports, 2026)

Comparative Chloroplast Genomics of Sugar Beet and Wild Relatives: Insights into Photosystem Gene Regulation and Stress Tolerance - Muhammad Sameeullah; Abdullah; Neelam Batool; Ibrar Ahmed; Mehmet Cengiz Baloglu; Noreen Aslam; Mehmet Örgeç; Ekrem Gurel; Mohammad Tahir Waheed; Songul Gurel (Functional & Integrative Genomics, 2026)

Mountain forests as climate mitigation solutions: Elevation and forest structure regulate carbon storage and indicative monetary carbon value - Shiekh Marifatul Haq; Muhammad Waheed; Ashutosh Kumar; Faten Zubair Filimban; Rainer W. Bussmann; Manoj Kumar (Forest Ecology and Management, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Advanced Modeling and Decision Support for Anti-Allergic Drugs Using Topological Indices and QSPR Analysis - Muhammad Waheed Rasheed; Abid Mahboob; Asima Parveen; Mona Bin-Asfour (Journal of Pharmaceutical Innovation, 2026)

Multibiomarker assessment of greenly synthesized silver nanoparticles toxicity in the Tor putitora - Noman Waheed; Adeeba Naseer; Sabahat Saeed; Muhammad Fiaz Khan; Yukun Zhang; Venkata Siva Naga Sai Goli (Marine Pollution Bulletin, 2026)

Comprehensive techno-economic assessment of commercial scale pyrolysis and co-pyrolysis plant of textile sludge and low-density polyethylene - Arslan Khan; Daniel Ciolkosz; Muhammad Safdar Ali; Waheed Miran; Imtiaz Ali (Process Safety and Environmental Protection, 2026)

A small-scale experimental prototype for exhaust heat-based mechanical energy harvesting in passenger vehicles, with extrapolation to heavy vehicles - Muhammad Bader Munir; Muhammad Waheed Ashraf; Najam ul Qadir; Sibghat Ullah; Allah Ditta (Next Research, 2026)

Integrated optimization of Lantana camara-based biopesticide for Sitophilus granarius control: Chemical profiling, residual efficacy, and machine-learning-driven decision support - Pervin Erdogan; Muhammad Aasim; Zemran Mustafa; Amjad Ali; Seyid Amjad Ali; Rashid Abbas Khan; Abdul Waheed (Journal of Stored Products Research, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Ecological drivers and conservation prioritization for Withania somnifera: integrating co-occurrence patterns and niche modeling in human-dominated landscapes - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal (Landscape and Ecological Engineering, 2026)

Lactiplantibacillus plantarum: Systems Biology of a Versatile Microbe - Yong Chen; Muhammad Rizwan; Asif Nawaz; Muhammad Ihtesham Waheed; Muhammad Waqas; Mati Ullah (Probiotics and Antimicrobial Proteins, 2026)

Comparative identification of abiotic stress-responsive differentially expressed genes in chickpea using unsupervised machine learning, and traditional meta-analysis - Mohammad Shafiq; Rimshah Sabir; Yossma Waheed; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Genes & Genomics, 2026)

Biochemical analysis and antimicrobial potential of Mastacembelus armatus epidermal mucus - Muhammad Saeed Khan; Shandana Ali; Muhammad Qasim; Farman Ullah Dawar; Waheed Ullah (Journal of Fish Biology, 2026)
The epidermal mucus of fish plays an important role in innate immunity, providing both physical and biochemical protection through a complex matrix of bioactive molecules. The present study explored the biochemical characterization, bactericidal, and fungicidal activities of Mastacembelus armatus (Zig‐Zag eel) epidermal mucus treated with Aeromonas hydrophila . Extracts of epidermal mucus (ethanolic and acidic) of Mastacembelus armatus showed antimicrobial activity against selected resistant bacteria and fungi. The zone of inhibition (ZOI), which was measured in millimetres, revealed differences in activity between different fungi and bacteria. The acidic extract demonstrated noticeably higher ZOI values against various MDR bacteria and fungi was more effective than the ethanolic extract. Strong peaks in the Fourier transform infrared (FTIR) spectrum of Mastacembelus armatus indicated the presence of metabolic components in the epidermal mucus. The O–H and N–H stretching vibrations, which are indicative of water content and protein‐based molecules such as mucins or amide, are shown by a large peak at 3272.60 cm −1 . This result suggests that fish epidermal mucus has the potential to contribute enormously to the defence of fish against bacteria and fungi. Therefore, this study could be evidence in favour of the substitution of chemical antibiotics with fish epidermal mucus as a new ‘antimicrobial’ introduced in aquaculture and in humans against bacterial infections.

Ethnobotanical documentation of plant resources used for women’s healthcare in Sahiwal division, Punjab, Pakistan - Kaniz Fatima; Muhammad Iqbal; Fahim Arshad; Mari Sumayli; Yehia Hazzazi; Mukhammadjon Matazimov; Muhammad Waheed (Genetic Resources and Crop Evolution, 2026)

Assessing stand development controls on carbon sequestration and carbon credit value in tropical introduced teak plantation - John Oluwafemi Ayoola; Babatunde Oluseyi Ajiboye; Abraham Olanrewaju Opanike; Fahim Arshad; Shiekh Marifatul Haq; Adetayo Olubunmi Odunola; Aderinola Adeola Deborah; Muhammad Waheed; Ismoilov Ibrokhim; Muydinov Nurillo Tukhtarovich; Tursunqulov Jasur Baxtiyorovich; Mamatov Hurshidbek Mirzakamol o‘g‘li (Environmental Monitoring and Assessment, 2026)

Species composition, relative abundance and seasonal variation of medically important mosquitoes in district Bajaur, Khyber Pakhtunkhwa, Pakistan - Halimullah; Waleeja Tur Rabbia; Naveeda Akhtar Qureshi; Waheed Ali Panhwar; Sajid Malik; Muhammad Ilyas (Acta Parasitologica, 2026)

Probiotics unveiled: bridging general health benefits to the era of precision medicine - Mati Ullah; Muhammad Rizwan; Muhammad Ihtesham Waheed; Muhammad Shoaib Alam; Sami Ullah Jan; Ali Raza; Muhammad Faisal Shahid; Vivian Andoh; Yong Chen (World Journal of Microbiology and Biotechnology, 2026)

Entomocidal effect of green synthesized titanium dioxide nanoparticles using Aloe vera Extract against Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2026)

Spatial coupling of landscape resistance and socioecological threats to endangered Punjab Urial in the semi-arid Potohar Plateau - Maria Neelam; Asma Jabeen; Muhammad Waheed; Sanaullah Sattar; Graciela Dolores Avila-Quezada; Abeer Hashem; Elsayed Fathi Abd_Allah (Journal of Arid Environments, 2026)

Erratum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdual Waheed Rabbni; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Corrigendum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdul Waheed Rabbani; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Biodiversity under threat: the role of native and alien indicator species in assessing forest disturbance and conservation needs - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Asma Jabeen; Alessandra De Marco (Biological Invasions, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Genetic dissection on polyphenol oxidase activity and yellow pigment content in wheat grains during different development stages - Yingxin Guo; Dehua Wang; Qianqian Lv; Xiaojie Yang; Guanying Wang; Muhammad Waheed Riaz; Xin Guo; Jichun Tian; Zhiying Deng (Euphytica, 2026)

The Influence of Policy Indicators on Circular Economy Metrics in Australia: Application of Asymmetric Analysis - Suleman Sarwar; Afifa Qadeer; Rida Waheed; Ghazala Aziz; Muhammad Wasim Hussan (Circular Economy and Sustainability, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

The first complete genome sequence of a highly pathogenic fowl adenovirus serotype 4 isolate from an infected chicken in Pakistan reveals the absence of a natural large genomic deletion - Salman Ahmad; Syeda Fakhra Waheed; Itra Ayoub; Ayesha Siddiqua; Soban Tufail; Sofia Irfan; Raheem Ullah; Muhammad Salahuddin Shah; Mazhar Iqbal; Moazur Rahman; Aamir Shehzad (Archives of Virology, 2026)

Seasonal shifts in algal communities driven by environmental gradients in Kallar Kahar Lake, Pakistan - Mubashrah Munir; Rahmatullah Qureshi; Fahim Arshad; Asma Jabeen; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah; Muhammad Waheed (Limnology, 2026)

Heavy metal contamination in agricultural soils: an environmental and food safety perspective - Siraj ud Din; Muhammad Subhanullah; Bakht Rawan; Shahla Nazneen; Muhammad Ilyas; Thiago Machado da Silva Acioly; Waheed Ullah; Abdullah Faiz Al Asmari; Saiful Islam (Environmental Monitoring and Assessment, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Synergistic Effect of Biochar and Bacillus Subtilis on the Development of Colletotrichum Graminicola in Maize - Nimra Nadeem; Adnan Akhter; Waheed Anwar; Tehmina Anjum; Muhammad Khurshid; Nasir Ali; Sana Javed; Hibba Arshad (Journal of Soil Science and Plant Nutrition, 2026)

Molecular evaluation of superior agronomic traits in local wheat germplasm using functional markers - Muhammad Qamar Ashfaq; Andleeb Anjum Qazalbash; Tayyaba Shaheen; Arzish Javaid; M. Qandeel Waheed; Anjuman Arif (Genetic Resources and Crop Evolution, 2026)

Genome-wide identification, functions, and expression analysis of carbonic anhydrase gene family in the gills of O. niloticus under salinity stress - Ahmad Waheed; Samra Farooq; Jabbir Ali Khan; Imran Ahmad Khan; Samra Shafqat; Hina Naz; Muhammad Saleem Khan; Muhammad Wajid (Aquaculture, 2026)

Multifunctional bio-composite hydrogels: PolyAMPs-tuned hydroxyapatite-PVA/gelatin systems development and characterization - Anum Ayub Awan; Waheed Miran; Muhammad Bilal Khan Niazi; Zakir Hussain; Aqeel Afzal; Usman Liaqat (Sustainable Chemistry and Pharmacy, 2026)

Deep neural networks reveal organic pollutants’ dominance in global inflammatory bowel disease - Iman Waheed Khan; Muhammad Mueed Khan; Anthony Donato (Journal of Environmental Sciences, 2026)

Corrigendum to ‘Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads’ [International Journal of Refrigeration 181 (2026) 111–125] - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Carbon sequestration and credit potential of native and non-native monoculture plantations in a subtropical irrigated forest - Muhammad Waheed; Shiekh Marifatul Haq; Abeer Al-Andal; Fahim Arshad; Muhammad Iqbal (Biomass and Bioenergy, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Harnessing Genetic Innovations for Climate-Resilient and High-Yield Crops: A Pathway to Sustainable Agriculture - Xu Qiao; Abdul Waheed; Cui Dong; Aishajiang Aili; Murad Muhammad; Hailiang Xu (Plant and Soil, 2026)

Determination of the Chemical Profile of Hibiscus rosa-sinensis L. Leaves Using Different Solvents and Evaluation of their Antioxidant, Antimitotic, and Antiproliferative Potentials - Sehrish Sadia; Muhammad Waheed; Tahira Rashid; Murad Muhammad; Huma Bashir; Fahim Arshad; Muhammad Iqbal; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd-Allah (Journal of Pharmaceutical Innovation, 2026)

In silico characterization and molecular docking of the MIOX gene in Nile tilapia (Oreochromis niloticus) - Samra Farooq; Samra Shafqat; Jabbir Ali Khan; Ahmad Waheed; Ali Umar; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2026)

Development of a Parametric Multi-Material Physics-Informed Neural Network for real-time heat transfer prediction in spherical tokamak divertor under transient heat loads - Habib Ur Rahman; Abid Hussain; Muhammad Ilyas; Lei Li; Khalid Waheed; Manzoor Ahmed (Annals of Nuclear Energy, 2026)

Geographic distribution patterns, population dynamics, and habitat vulnerability of endangered and endemic Trillium govanianum - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Raja Waqar Ahmed Khan; Amir Sohail (Environmental Monitoring and Assessment, 2026)

Impact of Aspergillus flavus infection on nutrient composition and storage quality of maize (Zea mays L.) using side needle inoculation - Imran Manzoor; Muhammad Arshad; Rao Muhammad Samran Gul; Ijaz Rasool Noorka; Momina Hussain; Muhammad Sajid; Noorah A. AlKubaisi; Sezai Ercisli; Mohamed S. Elshikh; Abdul Waheed (Journal of Stored Products Research, 2026)

Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Performance comparison and sustainability assessment of mesoporous FAU zeolites for the plastic upcycling - Muhammad Usman Azam; Nanbyen George Kim; Auguste Fernandes; M. Filipa Ribeiro; Waheed Afzal; Inês Graça (Chemical Engineering Journal, 2026)

Alien floral homogenizes the traditional knowledge diversity of isolated ethnic communities - Nausheen Niaz; Shiekh Marifatul Haq; Aadil Abdullah Khoja; Muhammad Waheed; Muhammad Azhar Jameel; Manzer H. Siddiqui; Ivana Vitasović-Kosić; Rainer W. Bussmann (Biological Invasions, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

Harnessing traditional ethnoveterinary practices and medicinal plants for sustainable livestock health in arid rangelands - Shumaila Batool; Murad Muhammad; Minahal Fatima; Muhammad Waheed; Muqadas Batool; Mona F. A. Dawood; Abdul Wahab; Abdul Waheed; Khalid Abbas (Genetic Resources and Crop Evolution, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Influence of cationic, anionic, and non-ionic surfactants on in-situ growth of polyaniline on alumina ceramic membranes for the effective crude oil-in-water emulsion separation: Experimental and machine learning approaches - Muhammad Saad Khan; Umair Baig; Abdul Waheed; Sohaib Abdelazem; Isam H. Aljundi (Desalination, 2025)

Plant root-mediated carbon sequestration and nutrient cycling in grassland ecosystems under land use and climate change - Abdul Waheed; Xu Qiao; Murad Muhammad; Yeernazhaer Yiremaikebayi; Xie Yingying; Hailiang Xu; Aishajiang Aili; Abdul Wahab (Agriculture, Ecosystems & Environment, 2025)

Alien flora of the Kingdom of Saudi Arabia: taxonomic composition, phylogenetic patterns, and invasion status - Shiekh Marifatul Haq; Muhammad Waheed; Muhammad Azhar Jameel; Łukasz Walas; M. Nasir Khan; Manzer H. Siddiqui; Saud Alamri; Anas E. AbuYahya; Rainer W. Bussmann (Biological Invasions, 2025)

Native plantations foster phylogenetic cohesion while nonnative plantations promote higher species turnover in understory vegetation in subtropical managed forest - Shoaib Ilyas; Sehrish Sadia; Mr Nadeem; Abeer Al-Andal; Asma Jabeen; Fahim Arshad; Sanaullah Sattar; Zarafshan Abbas; Muhammad Waheed (Journal of Environmental Management, 2025)

Quantitative exploration and conservation of the medicinal plant resources used by the inhabitants of Northern Pakistan - Murad Muhammad; Abdul Waheed; Abdul Wahab; Nimrah Ameen; Ibad Ullah; Muhammad Majeed; Muhammad Waheed; Khalid Rehman Hakeem; Mona F. A. Dawood; Wen-Jun Li (Genetic Resources and Crop Evolution, 2025)

Assessing alkaline battery waste toxicity in Nile tilapia (Oreochromis niloticus): integrating physiological biomarker analysis with molecular docking insights - Ahmad Waheed; Habiba Zafar; Hina Naz; Jabbir Ali Khan; Samra Shafqat; Muhammad Saleem Khan; Muhammad Wajid (Ecotoxicology, 2025)

Functional trait variability and adaptive strategies of Genus Carex along the elevation gradients - Muhammad Waheed; Fahim Arshad; Muhammad Manzoor; Syed Waseem Gillani; Abeer Al-Andal; Kaniz Fatima (Flora, 2025)

Experimental and CFD simulation of a printed circuit heat exchanger design - Muhammad Ali Khan; Muhammad Ilyas; Khalid Waheed; Inamul Haq; Fatih Aydogan (Annals of Nuclear Energy, 2025)

Endophytic Meyerozyma guilliermondii augmented growth attributes and metabolite production in Triticum aestivum under salinity stress - Zeeshan Khan; Muhammad Irshad; Anwar Hussain; Arshad Iqbal; Zamarud Shah; Waheed Murad; Eman R. Elsharkawy; Muhammad Nafees (Folia Microbiologica, 2025)

Trait plasticity and invasion success of Ageratum conyzoides in subtropical urban landscapes - Muhammad Waheed; Fahim Arshad; David M. Richardson; Abeer Al-Andal; Kaniz Fatima (Urban Ecosystems, 2025)

Taxonomic implications of pollen morphometric features for identification of arid and semi-arid arecaceae taxa - Hafiza Ayesha Rahim; Shabnum Shaheen; Muhammad Waheed; Nidaa Harun; Tahira Alyas; Fahim Arshad; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (Genetic Resources and Crop Evolution, 2025)

Finding the Best Growth Media for Kiwifruit Cv. ‘Hayward’ Seedling Rootstocks in Mansehra District, Pakistan - Sadaf Bibi; Aftab Afzal; Ghulam Mujtaba Shah; Abdul Waheed; Muhammad Anas; Waseem Ahmed Khattak; Shah Fahad (Applied Fruit Science, 2025)

Optimizing agroforestry systems through traditional ecological knowledge: a sustainable model for tree species selection in semi-arid lowland region - Muhammad Waheed; Fahim Arshad; Kaniz Fatima; Asma Jabeen; Abeer Al-Andal; Abdullayev Abdulla Fayzulla Ugli; Baxtigul Nurullayeva; Oygul Khujaniyozova (Agroforestry Systems, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Geo-spatial distribution of air pollutants in urban area and its potential health risk analysis solutions - Fajar Waheed; Nusrat Ehsan; Rabiya Nasir; Waqas Ahmed Khan; Muhammad Fahim Khokhar; Laila Shahzad; Aqil Tariq; Hira Afzal; Qamar uz Zaman (Urban Climate, 2025)

Dynamics of bi-susceptibility patterns in Covid-19 outbreaks and associated abstain strategies - Waheed Ahmad; Muhammad Rafiq; Azhar Iqbal Kashif Butt; Momina Zainab; Naeed Ahmad (Modeling Earth Systems and Environment, 2025)

Exploring the hidden world of muskmelon miRNAs: experimental hunts of computational predicted miRNAs and their protein targets - Abdul Ghaffar; Naqeebullah Khan; Irshad Ali; Attiq ur Rehman; Samiullah; Waheed Ahmed Shah; Muhammad Javed Khan (Genetic Resources and Crop Evolution, 2025)

Meta-analysis of RNA-seq data of soybean under heat, water, and drought stresses - Mohammad Shafiq; Farrukh Azeem; Yossma Waheed; Igor Eduardovich Pamirsky; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Plant Biotechnology Reports, 2025)

Identification and Characterization of Evolutionary Conserved Muskmelon Non-coding miRNAs and Their Target Proteins - Abdul Ghaffar; Naqeebullah khan; Muhammad Zafar Saleem; Irshad Ali; Attiq Ur Rehman; Waheed Ahmed Shah; Samiullah (Biochemical Genetics, 2025)

Food security and economic resilience of wild snake gourd (Trichosanthes cucumerina subsp. Cucumerina) under different host trees in subtropical managed forests - Muhammad Waheed; Fahim Arshad; Murad Muhammad; Abeer Hashem; Mohamad Alnafissa; Elsayed Fathi Abd-Allah; Valisher Sapayev (Agroforestry Systems, 2025)

Conserving the critically endangered Hangul (Cervus hanglu hanglu)—future distribution and efficiency of protected areas under climate change - Shiekh Marifatul Haq; Muhammad Waheed; Łukasz Walas; Shirin Alipour; Riyaz Ahmad; Rainer W. Bussmann; Mohammad K. Al-Sadoon (Environmental Monitoring and Assessment, 2025)

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Dynamic approaches to ecological restoration in China's mining regions: A scientific review - Hailiang Xu; Abdul Waheed; Amannisa Kuerban; Murad Muhammad; Aishajiang Aili (Ecological Engineering, 2025)

Invasion by the non-native tree Vachellia farnesiana alters the understory composition of plants and soil properties in a managed forest in the subtropical region of Pakistan - Muhammad Waheed; Shiekh Marifatul Haq; Fahim Arshad; David M. Richardson (Plant Ecology, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Correction: Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Delving Into Nanoparticle Systems for Enhanced Drug Delivery Technologies - Nimra Abaidullah; Khalid Muhammad; Yasir Waheed (AAPS PharmSciTech, 2025)

Mitigation of cadmium stress by salicylic acid: Physiological and biochemical responses in NM-2006, NM-92, and Mash-88 mung bean varieties - Abdul Waheed; Qin Zhang; Hailiang Xu; Haitao Dou; Murad Muhammad; Aishajiang Aili; Mohammed O Alshaharni (Journal of Hazardous Materials, 2025)

Adaptive floristic diversity and ecological responses to environmental gradients in the saline soil ecosystem - Sehrish Sadia; Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Mubashrah Munir; Asma Jabeen; Samreen Aslam (Journal for Nature Conservation, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Morphology and multigene phylogeny revealed four new species of Agaricus section Minores from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Hira Bashir; Shah Hussain (Mycological Progress, 2025)

Development of a dispersive liquid–liquid microextraction technique for ultra-sensitive detection of gold in environmental samples using atomic absorption spectrometry - Waheed Ali Soomro; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani; Zulfiqar Ali Bhatti; Rafi-u-Zaman Brohi; Imran Khan Rind (Environmental Monitoring and Assessment, 2025)

Corrigendum to “Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies” [Trends in Food Science & Technology 153 (2024) 104695] - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2025)

Maillard-derived mung bean protein-peach gum conjugates: A novel emulsifier to improve stability, antioxidants, and physicochemical properties of chia seed oil nanoemulsion - Mahbuba Siddiquy; Qais Ali Al-Maqtari; Mohamed Ghamry; Hazem Golshany; Norzila Othman; Amer Ali Mahdi; Yiasmin Mst Nushrat; Muhammad Waheed Iqbal; Lianfu Zhang (Food Research International, 2025)

Expert perceptions on CPEC sustainability appraisal: SWOT analysis for informed policy decisions - Abdul Waheed; Sajida Kousar; Muhammad Irfan Khan; Thomas Bernward Fischer (Environmental Science & Policy, 2025)

Biochar in sustainable agriculture and Climate Mitigation: Mechanisms, challenges, and applications in the circular bioeconomy - Abdul Waheed; Hailiang Xu; Xu Qiao; Aishajiang Aili; Yeernazhaer Yiremaikebayi; Dou Haitao; Murad Muhammad (Biomass and Bioenergy, 2025)

Optimization-based innovative approach for economical design of reinforced concrete isolated footings - Junaid Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mansoor Shakeel (Innovative Infrastructure Solutions, 2025)

Navigating Climate Change: Exploring the Dynamics Between Plant–Soil Microbiomes and Their Impact on Plant Growth and Productivity - Murad Muhammad; Abdul Wahab; Abdul Waheed; Khalid Rehman Hakeem; Heba Ibrahim Mohamed; Abdul Basit; Muhammad Danish Toor; Yong‐Hong Liu; Li Li; Wen‐Jun Li (Global Change Biology, 2025)
Understanding the intricate interplay between plant and soil microbiomes and their effects on plant growth and productivity is vital in a rapidly changing climate. This review explores the interconnected impacts of climate change on plant–soil microbiomes and their profound effects on agricultural productivity. The ongoing rise in global temperatures, shifting precipitation patterns and extreme weather events significantly affect the composition and function of microbial communities in the rhizosphere. Changes in microbial diversity and activity due to rising temperatures impact nutrient cycling, microbial enzyme synthesis, soil health and pest and disease management. These changes also influence the dynamics of soil microbe communities and their capability to promote plant health. As the climate changes, plants' adaptive capacity and microbial partners become increasingly crucial for sustaining agriculture. Mitigating the adverse effects of climate change on plant growth and agricultural productivity requires a comprehensive understanding of the interconnected mechanisms driving these processes. It highlights various strategies for mitigating and adapting to environmental challenges, including soil management, stress‐tolerant crops, cover cropping, sustainable land and water management, crop rotation, organic amendments and the development of climate‐resilient crop varieties. It emphasises the need for further exploration of plant–soil microbiomes within the broader context of climate change. Promising mitigation strategies, including precision agriculture and targeted microbiome modifications, offer valuable pathways for future research and practical implementation of global food security and climate change.

GIS-based spatial assessment of water quality, soil, and plant: a case study of Darawat Dam Sindh, Pakistan - Muhammad Farooque Lanjwani; Muhammad Yar Khuhawar; Rafi-O.-zaman Brohi; Waheed Ali Soomro; Abdul Hameed Lanjwani; Muhammad Umar Lanjwani (Environmental Monitoring and Assessment, 2025)

Unlocking the structure-activity relationship of hierarchical MFI zeolites towards the hydrocracking of HDPE - Muhammad Usman Azam; Auguste Fernandes; Maria João Ferreira; Alan J. McCue; Inês Graça; Waheed Afzal (Fuel, 2025)

Co-encapsulation of borage seed oil and peppermint oil blends within ultrasound-assisted soy protein isolate/purity gum ultra complex nanoparticles: Fabrication, structural interaction mechanisms, and in vitro digestion studies - Abdur Rehman; Ibrahim Khalifa; Hafiz Abdul Rasheed; Muhammad Waheed Iqbal; Muhammad Shoaib; Junxia Wang; Yongjun Zhao; Qiufang Liang; Mingming Zhong; Yufan Sun; Tawfiq Alsulami; Xiaofeng Ren; et al. (Food Chemistry, 2025)

Decoding genetic diversity and population structure of Brassica species by inter primer binding site (iPBS) retrotransposon markers - Muhammad Sameeullah; Fatma Kayaçetin; Khalid Mahmood Khavar; Achmad Yozar Perkasa; Siti Maesaroh; Mohammad Tahir Waheed; Vahdettin Çiftçi (Genetic Resources and Crop Evolution, 2025)
Marker-assisted breeding serves as a potent tool for screening target germplasm, assessing genetic diversity, and determining breeding potential of a crop. Therefore, inter primer binding site (iPBS)-retrotransposons marker system was employed to evaluate a collection of 33 Brassica genotypes, including 10 Brassica juncea , 5 B. oleracea , 7 Sinapis alba , 5 B. nigra , and 6 B. rapa , were utilized to evaluate their genetic diversity and variations 10 polymorphic primers that generated a total of 144 bands. Various diversity indices were calculated in the studied germplasm, including polymorphism information content (0.13–0.30), effective number of alleles (1.217–1.689), Shannon’s information index (0.244–0.531), and gene diversity (0.148–0.370). These indices collectively affirmed substantial genetic variations within the germplasm. Molecular variance analysis revealed that the majority (62%) of genetic variations were present within populations. The Brassica accessions were categorized into three populations utilizing a model-based structure algorithm. Evaluation of diversity indices based on the structure indicated that populations III and II exhibited higher diversity. Principal coordinate analysis and neighbor-joining analysis further corroborated the three distinct populations, confirming the reliability of the STRUCTURE analysis. Notably, the genetic distance assessment identified BN1 and BN3 from B. nigra species and the genotypes BO1 and BO3 from B . oleracea as genetically diverse mustard accessions. The extensive genetic diversity observed within the Brassica germplasm underscores its significance as a valuable genetic resource for comprehensive Brassica breeding programs. Moreover, these accessions hold promise as suitable candidates for heterosis breeding initiatives aimed at improving mustard production.

Zinc-lysine and iron-lysine mitigate chromium toxicity in pearl millet (Pennisetum glaucum) through modulating photosynthetic and antioxidant system and inhibiting chromium uptake and translocation - Zaryab Ali Abbass; Maryam Zahra; Habib Ali; Muhammad Javed; Imran Mahmood; Mavadat Hussain Alvi; Alishba Waheed; Sadam Hussain; Sachin Kumar (Environmental Science and Pollution Research, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

The genus Hymenagaricus: phylogeny, time divergence estimation, and the description of three new species from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Shah Hussain (Mycological Progress, 2024)

Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2024)

Reorientation of energy policy and management: Integrated Energy Planning (IEP) framework implementation for Renewable and Thermal Energy Systems (RTES) - Humera Tubussum; Muhammad Aslam; Hezlina Mohd Hashim; Maran Marimuthu; K.H. Mahmoud; Abdullah Saad Alsubaie; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi; Awais Bokhari; Abdul-Sattar Nizami (Process Safety and Environmental Protection, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Investigation of therapeutic potential of the Il24-p20 fusion protein against breast cancer: an in-silico approach - Shahnila Qureshi; Nadeem Ahmed; Hafiz Muhammad Rehman; Muhammad Imran Amirzada; Fiza Saleem; Kainat Waheed; Afeefa Chaudhry; Iram Kafait; Muhammad Akram; Hamid Bashir (In Silico Pharmacology, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Harnessing bacterial endophytes for environmental resilience and agricultural sustainability - Murad Muhammad; Abdul Wahab; Abdul Waheed; Heba Ibrahim Mohamed; Khalid Rehman Hakeem; Li Li; Wen-Jun Li (Journal of Environmental Management, 2024)

Characterization and Induction of Biochar Induced Capsicum annumm Defense Against Bacterial Wilt - Muhammad Taqqi Abbas; Tehmina Anjum; Waheed Anwar; Muhammad Khurshid; Adnan Akhter (Journal of Soil Science and Plant Nutrition, 2024)

Skipping irrigation at pre- and post-anthesis stages influences grain yield and starch contents of bread wheat derived from synthetic or landraces - Sajid Shokat; Mian Abdur Rehman Arif; Muhammad Qandeel Waheed; Fulai Liu; Carlos Guzmán; Sukhwinder Singh (Cereal Research Communications, 2024)
This study aims to evaluate the role of genetic diversity originated from three-way crosses of landraces and synthetic bread wheat derivatives attempted with elite cultivars to identify the genotypes having better grain yield as well as better starch contents under flowering stage drought stress. In total, 50 genotypes comprised of 47 derivatives of landraces and synthetics, and three standard varieties were grown in the fields of CIMMYT, Obregon following alpha lattice design with two replications. Drought stress was imposed by stopping the irrigation before anthesis and post-anthesis stages. Different traits related to physiological adaptations, earliness, grain yield and starch contents were decreased under drought stress except amylose which increased significantly. Canopy temperature depression was not significantly affected by drought stress. Further, we identified strong correlation of grain yield with plant height, normalized difference in vegetation index, plant maturity, spike length, grain number and thousand grain weight but negative with canopy temperature depression. Non-significant correlation of amylose and amylopectin was recorded with grain yield. Results revealed that genetic diversity derived from landraces and synthetic bread wheat can improve grain yield and starch contents but simultaneous improvement of both is elusive.

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Biosensor-assisted evolution of RhaD for enhancing the biosynthetic yield of d-allulose - Beini Chen; Xinrui Tang; Yufei Zhang; Hossain M. Zabed; Yuvaraj Ravikumar; Muhammad Waheed Iqbal; Jiayin Wang; Mei Zhao; Xianghui Qi (Food Bioscience, 2024)

Adaptive convergence and divergence underpin the diversity of Asteraceae in a semi-arid lowland region - Muhammad Waheed; Fahim Arshad (Flora, 2024)

Surviving chlorinated waters: bleaching sensitivity and persistence of free-living amoebae - Muhammad Tariq Zahid; Ghulam Mustafa; Romasa Sajid; Ayesha Razzaq; Muzdalfa Waheed; Moonis Ali Khan; Jae-Hoon Hwang; Young Kwon Park; Woo Jin Chung; Byong-hun Jeon (Environmental Science and Pollution Research, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Risk identification of salts and heavy metals in water by multivariate statistical techniques and GIS based interpolation: A case study of Saeedabad, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Ahsan Habib; Muhammad Farooque Lanjwani; Waheed Ali Soomro; Ghamshan Suther; Wenbin Liu (Regional Studies in Marine Science, 2024)

Nano-based remediation strategies for micro and nanoplastic pollution - Nayab Batool Rizvi; Adnan Sarwar; Saba Waheed; Zeenat Fatima Iqbal; Muhammad Imran; Ayesha Javaid; Tak H. Kim; Muhammad Shahzeb Khan (Journal of Contaminant Hydrology, 2024)

Food ethnobotany of forest resource in the high-altitude Himalaya Mountains: Enhancing the food sovereignty of ethnic groups - Shiekh Marifatul Haq; Aadil Abdullah Khoja; Muhammad Waheed; Manzer H. Siddiqui; Saud Alamri; Alanoud T. Alfagham; Latifah A. AL-Humaid; Rainer W. Bussmann (Forest Policy and Economics, 2024)

Inhibitory potential of Syzygium aromaticum against Fusarium oxysporum f. sp. lycopersici: In-vitro analysis and molecular docking studies - Muhammad Atif; Tehmina Anjum; Ahmad Ali Shahid; Ahmad Hassan; Waheed Akram (South African Journal of Botany, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Heavy Metal Stress in Medicinal Plants: Detoxification Mechanisms, Antioxidants, and Implications for Human Health - Muhammad Waheed Riaz; Tong Wu; Quaid Hussain; Fasih Ullah Haider; Weiwei Jiang; Qingsong Shao; Muhammad Aamir Manzoor; Bingcong Xing (Journal of Soil Science and Plant Nutrition, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Impact of climate change awareness on household attitude toward food waste reduction - Chimeziem Elijah Nwankwo-Ojionu; Nor Azura Adzharuddin; Moniza Waheed; Azlina Mohd Khir; Muhammad Mansur Abdulwakil; Chioma Mercy Chimeziem Ehiemere (Journal of Environmental Studies and Sciences, 2024)

ANN and regression based quantification framework for climate change impact assessment on a weak transmission grid of a developing country across Horizon 2050 plus - M. Mahad Malik; Hamza Waheed Asim; Syed Ali Abbas Kazmi; Kamran Mujahid; Muhammad Waleed Ansari (Environment, Development and Sustainability, 2024)

Investigating the quantum size effects of multi-walled carbon nanotubes (MWCNTs) in photocatalytic fermentative biohydrogen production - Hina Ramzan; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Muneeb Ur Rahman; Fuhua Shen; Zhiping Zhang; Reeta Rani Singhania; Farzana Jabeen; Waheed Afzal; Nadeem Tahir (Journal of Cleaner Production, 2024)

“Traditional” use in a global world: unsustainable ethnozoological usage among Himalayan ethnic groups drives species to extinction - Shiekh Marifatul Haq; Muhammad Waheed; Rainer W. Bussmann (Biodiversity and Conservation, 2024)

Isolation and characterization of PGPR obtained from different arsenic-contaminated soil samples and their effect on photosynthetic characters of maize grown under arsenic stress - Zainab Waheed; Sumera Iqbal; Muhammad Irfan; Khajista Jabeen; Noshin Ilyas; Wahidah H. Al-Qahtani (Environmental Science and Pollution Research, 2024)

Digital transformation, supplier concentration, and CEO financial experience: Unveiling the dynamics of innovation performance in Chinese firms - Hua Zhang; Xiaohui Wang; Muhammad Waheed Akhtar (Journal of Cleaner Production, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

2D Ti3C2Tx-MXene nanosheets and graphene oxide based highly sensitive humidity sensor for wearable and flexible electronics - Waqas Waheed; Shoaib Anwer; Muhammad Umair Khan; Muhammad Sajjad; Anas Alazzam (Chemical Engineering Journal, 2024)

Experimental and numerical study of an innovative twined tube HX design - Muhammad Ali Khan; Muhammad Daniyal Khalid; Muhammad Ilyas; Muhammad Daniyal Nauman; Muhammad Asim; Khalid Waheed; Fatih Aydogan (Annals of Nuclear Energy, 2024)

Water quality index and geographic information system to assess the groundwater quality of taluka Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Muhammad Farooque Lanjwani; Waheed Ali Soomro (Arabian Journal of Geosciences, 2024)

Evaluating the symmetric and asymmetric effectiveness of low carbon energy consumption for ecological footprint in China: the role of environment-related technological innovation - Xin Jin; Cheng Guo; Waheed Ahmad; Muhammad Sajid Ameen; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

Turbid reefs experience lower coral bleaching effects in NE Borneo (Sabah, Malaysia) - Allia Rosedy; Isabel Ives; Zarinah Waheed; Muhammad Ali Syed Hussein; Sindia Sosdian; Kenneth Johnson; Nadia Santodomingo (Regional Studies in Marine Science, 2023)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Climate change reshaping plant-fungal interaction - Abdul Waheed; Yakoopjan Haxim; Waqar Islam; Mushtaq Ahmad; Murad Muhammad; Fatmah M. Alqahtani; Mohamed Hashem; Haron Salih; Daoyuan Zhang (Environmental Research, 2023)

Bioimaging-guided discrimination of normal/cancer cells using Ag+-mediated red fluorescent carbon dots - Farid Ahmed; Weiqing Xu; Muhammad Muzammal Hussain; Waheed Ullah Khan; Hai Xiong (Chemical Engineering Journal, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Pseudomonas fluorescens and L-tryptophan application triggered the phytoremediation potential of sunflower (Heliantus annuus L.) in lead-contaminated soil - Muhammad Tauseef Jaffar; Zain Mushtaq; Abdul Waheed; Hafiz Naeem Asghar; Jianguo Zhang; Jiale Han (Environmental Science and Pollution Research, 2023)

Green synthesis of a mesoporous hyper-cross-linked polyamide/polyamine 3D network through Michael addition for the treatment of heavy metals and organic dyes contaminated wastewater - Abdul Waheed; Muhammad Sajid; Mohammad Asif (Chemosphere, 2023)

Recent trends in material design and preparation with structure-activity relationship for gold recovery from E-waste: A review - Mudasir Ahmad; Tariq Shah; Muhammad Rizwan Tariq; Lei Zhang; Yanting Lyu; Waheed Iqbal; Mehraj ud-din Naik; Ajit Khosla; Qiuyu Zhang; Baoliang Zhang (Journal of Cleaner Production, 2023)

Bactericidal role of epidermal mucus of freshwater fish treated with Aeromonas hydrophila - Shandana Ali; Syed Ata Ur Rahman Shah; Muhammad Rauf; Maizom Hassan; Waheed Ullah; Farman Ullah Dawar (Journal of Fish Diseases, 2023)
This study explored the bactericidal role of the epidermal mucus (EM) of five freshwater Cyprinid fish species namely Ctenopharyngodon idella , Labeo rohita , Catla catla , Hypophthalmichthys molitrix , and Cirrhinus mrigala after treatment with Aeromonas hydrophila . Extracts of EM (crude and acidic) of each species showed bactericidal activity against various Gram −ve ( Pseudomonas aeruginosa , Escherichia coli , Aeromonas hydrophila , Edwardsiella tarda , Salmonella enterica , Klebsiella pneumonia , Serratia marcescens , and Enterobacter cloacae ) and Gram +ve ( Bacillus wiedmannii and Staphylococcus aureus ) bacteria compared with standard antibiotics (Fosfomycin). The zone of inhibition (ZOI) was measured in millimetres against antibiotics (Fosfomycin). Variations in bactericidal activity of EM were observed against bacteria from the same and different fish species. The acidic extract was more effective than the crude extract and showed significantly higher ZOI values against various bacteria and Fosfomycin antibiotics. This result shows that fish EM may perform an important role in fish defence against bacteria. Therefore, this study may hint towards the substitution of synthetic antibiotics with fish EM that may be used as a novel ‘bactericidal’ in aquaculture as well as in humans against bacterial infections.

Emerging trends of green hydrogen and sustainable environment in the case of Australia - Afifa Qadeer; Muhammad Wasim Hussan; Ghazala Aziz; Rida Waheed; Suleman Sarwar (Environmental Science and Pollution Research, 2023)

MXene-based 2D Ti3C2Tx nanosheets for highly efficient cadmium (Cd2+) adsorption - Muhammad Ilyas; Mohammad Younas; Mansoor Ul Hassan Shah; Waheed Ur Rehman; Amin Ur Rehman; Zhi-Hua Yuan; Yu-Ming Zheng; Mahdi Sheikh; Mashallah Rezakazemi (Journal of Water Process Engineering, 2023)

Hydrocracking of surgical face masks over Y Zeolites: Catalyst development, process design and life cycle assessment - Muhammad Usman Azam; Auguste Fernandes; Inês Graça; Waheed Afzal (Fuel, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

Disaster management and environmental policy integration in Pakistan — an evaluation with particular reference to the China–Pakistan Economic Corridor Plan - Abdul Waheed; Thomas Bernward Fischer; Sajida Kousar; Muhammad Irfan Khan (Environmental Science and Pollution Research, 2023)

Wood as a green and sustainable alternative for environmentally friendly & flexible electronic devices - Hizbullah Malik; Muhammad Bilal Khan Niazi; Waheed Miran; Ahmed M. Tawfeek; Zaib Jahan; Emadeldin M. Kamel; Nouman Ahmed; Muhammad Saeed Akhtar (Chemosphere, 2023)

The deteriorating effects of cadmium accumulation on the yield and quality of maize crops - Naila Shah; Muhammad Irshad; Anwar Hussain; Asif Mehmood; Waheed Murad; Muhammad Qadir; Muhammad Awais; Mohib Shah; Naeem Khan (South African Journal of Botany, 2023)

Improving Nitrogen Acquisition and Utilization Through Root Architecture Remodelling: Insight from Legumes - Muhammad Nadeem; Muhammad Yahya; Jingyang Tong; Liaqut Shah; Sana Ullah Khan; Ahmad Ali; Alam Sher; Najeeb Ullah; Abdul Waheed (Journal of Plant Growth Regulation, 2023)
In crop species, nutrient deficiency severely damages plant growth and developmental processes, leading to end-yield penalties. Root architecture remodelling is considered a key factor underpinning nutrient-poor soil environments. Adequate nitrogen (N) supply can play a significant role in sustaining crop productivity on nutrient-deficient soils. However, excessive application of nitrogenous fertilizer may pollute the soil and increase the production cost for the growers. To tackle this problem, crop breeders have made tremendous efforts to improve the N-use efficiency of agricultural crops. This article summarizes the recent progress in identifying QTLs/genes, regulatory pathways, and hormonal crosstalk involved in the growth and development of legumes roots system. Moreover, we have described the progress in microbe–root symbiosis via QTLs/genes regulations, which results in improved N acquisition. Understanding the molecular mechanisms that regulate the root architecture in response to N availability may help to strengthen the root system of legumes and promote environmental friendly and sustainable agriculture.

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Usage of the XGBoost and MARS algorithms for predicting body weight in Kajli sheep breed - Asim Faraz; Cem Tırınk; Hasan Önder; Uğur Şen; Hafiz Muhammad Ishaq; Nasir Ali Tauqir; Abdul Waheed; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2023)

Synergistic evaluation of co-torrefaction performance of rice husk and coffee bean ground blends for biosolid production for industrial fuel sustainability - Arshid Mahmood Ali; Abdul Waheed; Muhammad Shahbaz; Asif Ali Mirani; Khurram Shahzad; Abdulrahim Ahmad Al-Zahrani; Ayyaz Muhammad Nawaz; Aishah Binti Mahpudz (Fuel, 2023)

From forest floor to tree top: Partitioning of biomass and carbon stock in multiple strata of forest vegetation in Western Himalaya - Shiekh Marifatul Haq; Irfan Rashid; Muhammad Waheed; Anzar Ahmad Khuroo (Environmental Monitoring and Assessment, 2023)

Efficient resource utilization of the electricity distribution sector using nonparametric data envelopment analysis and influential factors - Majid Ikram; Muhammad Zahid Rafique; Kamel Si Mohammed; Rida Waheed; Diogo Ferraz (Utilities Policy, 2023)

Recent developments of Red/NIR carbon dots in biosensing, bioimaging, and tumor theranostics - Muhammad Muzammal Hussain; Waheed Ullah Khan; Farid Ahmed; Yen Wei; Hai Xiong (Chemical Engineering Journal, 2023)

An ultrasensitive colorimetric and fluorescent “turn-on” chemosensor based on Schiff base for the detection of Cu2+ in the aqueous medium - Sikandar Khan; Mian Muhammad; Abdul Waheed Kamran; Hamed M. Al-Saidi; Salman S. Alharthi; Jari S. Algethami (Environmental Monitoring and Assessment, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

Halotolerant bacterial biofilms for desalination and water treatment: a pilot study - Sadaf Jahan Gauhar; Aisha Waheed Qurashi; Iram Liaqat; Urooj Zafar; Muhammad Arshad Virk; Chaman Ara; Mehwish Faheem; Muhammad Mubin (Environmental Science and Pollution Research, 2023)

Estimation of genetic diversity using seed storage protein (SSP) profiling in wild and cultivated species of Cicer L - Uswah Khalid; Muhammad Qandeel Waheed; Najma Parveen; Mian Abdur Rehman Arif; Anjuman Arif (Molecular Biology Reports, 2023)

Cottonseed oil: A review of extraction techniques, physicochemical, functional, and nutritional properties - Tahreem Riaz; Muhammad Waheed Iqbal; Shahid Mahmood; Iqra Yasmin; Ali Ahmad Leghari; Abdur Rehman; Anam Mushtaq; Khubaib Ali; Muhammad Azam; Muhammad Bilal (Critical Reviews in Food Science and Nutrition, 2023)

Synthesis, characterization and adsorption behavior of modified cellulose nanocrystals towards different cationic dyes - Tariq Aziz; Arshad Farid; Sampath Chinnam; Fazal Haq; Mehwish Kiran; Ab Waheed Wani; Zeid A. Alothman; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Muhammad Saeed Akhtar (Chemosphere, 2023)

Impact of background colorations on growth, movement behavior, and some body physiological factors of Nile tilapia, Oreochromis niloticus - Ahmad Waheed; Hina Naz; Muhammad Wajid; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2023)

COVID-19, travel restrictions and environmental consequences - Muhammad Usman; Li Yuyan; Mudassir Husnain; Muhammad Waheed Akhtar (Environment, Development and Sustainability, 2023)

Molecular-level behavior induction in the constitutive modeling of swelling clayey soils – A review - Muhammad Abdul Waheed; Omar S. Baghabra Al-Amoudi; Mohammed A. Al-Osta; Habib-ur-Rehman Ahmed (Transportation Geotechnics, 2023)

Synthesis of co-polyamide reverse osmosis membrane constituting a linear aliphatic triamine and m-phenylenediamine for enhanced desalination performance - Abdul Waheed; Umair Baig; Asif Matin; Shehzada Muhammad Sajid Jillani; Naef A.A. Qasem; Isam H. Aljundi (Desalination, 2023)

Characterization of Azadirachta indica synthesized silver nanoparticles and its toxicity against Dusky cotton bug, Oxycarenus hyalinipennis Costa (Hemiptera:Lygaeidae) - Muhammad Javaid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Mirza Abdul Qayyum; Muhammad Arslan Khan (International Journal of Tropical Insect Science, 2023)

Two polyamines -responsive WRKY transcription factors from Anoectochilus roxburghii play opposite functions on flower development - Bingcong Xing; Siqi Wan; Liyang Su; Muhammad Waheed Riaz; Lihong Li; Yulin Ju; Wangshu Zhang; Ying Zheng; Qingsong Shao (Plant Science, 2023)

Determinants of CSR and green purchase intention: Mediating role of customer green psychology during COVID-19 pandemic - Wasim Ahmad; Rana Muhammad Sohail Jafar; Abdul Waheed; Huaping Sun; Sayed Sibtain Ali Shah Kazmi (Journal of Cleaner Production, 2023)

Enhancing the antibacterial activity of Lactobacillus reuteri against Escherichia coli by random mutagenesis and delineating its mechanism - Enyun Ma; Yingfeng An; Guoyan Zhang; Mei Zhao; Muhammad Waheed Iqbal; Hossain M. Zabed; Xianghui Qi (Food Bioscience, 2023)

Treatment of Anaerobically Digested Distillery Spent Wash Using Electrocoagulation with Al-SS-Al Electrode Configuration - Waheed Ali Khokhar; Muhammad Rizwan; Naveed Ahmed Qambrani (Water, Air, & Soil Pollution, 2023)

Spatial variability of hydrochemistry and health risk assessment of groundwater of taluka Hala, district Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Muhammad Farooque Lanjwani; Taj Muhammad Jahangir Khuhawar; Muhammad Soomar Samtio; Waheed Ali Soomro; Abdul Rehman Baloch (Arabian Journal of Geosciences, 2023)

Empirical relationship between creativity and carbon intensity: a case of OPEC countries - Ghazala Aziz; Suleman Sarwar; Muhammad Shahbaz; Muhammad Nasir Malik; Rida Waheed (Environmental Science and Pollution Research, 2022)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

Observed trends and variability of seasonal and annual precipitation in Pakistan during 1960–2016 - Azfar Hussain; Jianhua Cao; Shaukat Ali; Sher Muhammad; Waheed Ullah; Ishtiaq Hussain; Mobeen Akhtar; Xiuqin Wu; Yinghui Guan; Jinxing Zhou (International Journal of Climatology, 2022)
Long‐term precipitation monitoring plays a vital role in water resource management and disaster prevention and mitigation. This study assesses spatial and temporal trends in seasonal and annual precipitation in Pakistan between 1960 and 2016 at an interannual scale. The Mann–Kendall (MK) test, Sen's slope (SS) estimator, and Sequential Mann–Kendall (SQMK) test were employed to assess trends. Cluster analysis and L ‐moment approach were used to identify the homogenous precipitation regions. In general, increasing precipitation trends between 1960 and 2016 were evident. Results indicated increasing precipitation in winter, autumn, summer and annual scale at the rates of 0.20, 2.18, 5.16, and 10.89 mm·decade −1 , respectively. In spring, the precipitation trend shows a decreasing trend at −0.67 mm·decade −1 . Moreover, a significant decreasing trend occurred in winter in southern Pakistan. The overall increasing trends were more noticeable between 1960 and 1988, compared to the declining precipitation during 1989–2016. SQMK analysis indicates a clear downward trend in most regions during 1989–2016, except in autumn. Annual precipitation has increased topographically except at 500 m and 1,500 m during 1960–2016 with a significant increase of 1.37 mm·decade −1 at elevation

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Evaluation and projection of precipitation in Pakistan using the Coupled Model Intercomparison Project Phase 6 model simulations - Adnan Abbas; Safi Ullah; Waheed Ullah; Muhammad Waseem; Xin Dou; Chengyi Zhao; Aisha Karim; Jianting Zhu; Daniel Fiifi Tawia Hagan; Asher Samuel Bhatti; Gohar Ali (International Journal of Climatology, 2022)
This study aimed to evaluate the performance of global climate models (GCMs) from the family of the Coupled Model Intercomparison Project Phase 6 (CMIP6) in the historical simulation of precipitation and select the best performing GCMs for future projection of precipitation in Pakistan under multiple shared socioeconomic pathways (SSPs). The spatiotemporal performance of GCMs was evaluated against the Climate Research Unit (CRU) data in simulating annual precipitation during 1951–2014, using the Taylor diagram and interannual variability skill (IVS). Moreover, the modified Mann–Kendall (mMK) and Sen's slope estimator (SSE) tests were employed to estimate significant trends in future precipitation for the period 2015–2100. Based on the comprehensive ranking index (CRI), the HadGEM3‐GC31‐MM model has the highest skill in simulating precipitation distributions followed by EC‐Earth3‐Veg‐LR, CNRM‐ESM2‐1, MPI‐ESM1‐2‐HR, CNRM‐CM6‐1, MRI‐ESM2‐0, CNRM‐CM6‐1‐HR, EC‐Earth3‐Veg, MCM‐UA‐1‐0, INM‐CM5‐0, KACE‐1‐0‐G, CAMS‐CSM1‐0, and HadGEM3‐GC31‐LL models. Furthermore, the projections of the best models ensemble mean (BMEM) showed that the study region will experience a substantial increase in precipitation under SSP3‐7.0 and SSP5‐8.5 but an indolent rise under SSP1‐2.6 and SSP2‐4.5 scenarios. The summer and annual precipitations exhibit a statistically significant increasing trend relative to the winter season under most scenarios. Moreover, the magnitude of monotonic trends in seasonal and annual precipitation progresses from low forcing scenario (SSP1‐2.6) to high forcing scenario (SSP5‐8.5). The findings of the study could provide a benchmark in selecting appropriate GCMs for future projection over a data scare region, like Pakistan. Moreover, the projected trends of future precipitation are crucial in devising adaption and mitigation actions towards sustainable planning of water resource management, food security, and disaster risk management.

Fresh evidence on connectedness between prominent markets during COVID-19 pandemic - Ijaz Younis; Besma Hkiri; Waheed Ullah Shah; Fiza Qureshi; Muhammad Ilyas; Cheng Longsheng (Environmental Science and Pollution Research, 2022)

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

Characterization and Utilization of Cow Manure Biochar as Soil Amendment for the Management of Northern Corn Leaf Blight - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Adnan Akhter; Tehmina Bahar; Waheed Anwar; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2022)

Isolation of the 3β-HSD promoter from Digitalis ferruginea subsp. ferruginea and its functional characterization in Arabidopsis thaliana - Noreen Aslam; Muhammad Sameeullah; Muhammet Yildirim; Mehmet Cengiz Baloglu; Buhara Yucesan; Andreas G. Lössl; Mohammad Tahir Waheed; Ekrem Gurel (Molecular Biology Reports, 2022)

Biocidal activity of green synthesized silver nanoformulation by Azadirachta indica extract a biorational approach against notorious cotton pest whitefly, Bemisia tabaci (Homoptera; Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

From the COVID-19 pandemic to corrupt practices: a tale of two evils - Muhammad Usman; Mudassir Husnain; Muhammad Waheed Akhtar; Yameen Ali; Areej Riaz; Aimon Riaz (Environmental Science and Pollution Research, 2022)

Mechanical and durability properties of fly-ash cement sand composite bricks: an alternative to conventional burnt clay bricks - Azaz Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mohamed Zawam (Innovative Infrastructure Solutions, 2022)

Designing Fusion Molecules from Antigens of Mycobacterium tuberculosis to Enhance Serodiagnostic Sensitivity in Latent TB Infection and Active TB State - Chandni Yaqoob; Saher Shahid; Aasia Khaliq; Zaib un Nisa; Imran H. Khan; Muhammad Waheed Akhtar (International Journal of Peptide Research and Therapeutics, 2022)

Genetic basis of some physiological traits and yield in early and late sowing conditions in bread wheat (Triticum aestivum L.) - Mian Abdur Rehman Arif; Maryam Liaqat; Muhammad Imran; Muhammad Qandeel Waheed; Anjuman Arif; Sukhwinder Singh; Sajid Shokat (Journal of Applied Genetics, 2021)

Asymmetric effects of premature deagriculturalization on economic growth and CO2 emissions: fresh evidence from Pakistan - Sana Ullah; Waheed Ahmad; Muhammad Tariq Majeed; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Hydrogeochemical and health risk investigation of potentially toxic elements in groundwater along River Sutlej floodplain in Punjab, Pakistan - Sajjad Ahmad; Muhammad Imran; Behzad Murtaza; Natasha; Muhammad Arshad; Rab Nawaz; Abdul Waheed; Hafiz Mohkum Hammad; Muhammad Asif Naeem; Muhammad Shahid; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2021)

Pseudocitrobacter anthropi reduces heavy metal uptake and improves phytohormones and antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Waheed Murad; Muhammad Irshad; Muhammad Qadir; Ho-Youn Kim (World Journal of Microbiology and Biotechnology, 2021)

Analyzing the determinants of clean energy consumption in a sustainability strategy: evidence from EU-28 countries - Muhammad Usman; Zhiqiang Ma; Muhammad Wasif Zafar; Abdul Waheed; Mingxing Li (Environmental Science and Pollution Research, 2021)

Assessment of the simulated aerosol optical properties and regional meteorology using WRF-Chem model - Gohar Ali; Yansong Bao; Birhanu Asmerom; Waheed Ullah; Safi Ullah; Muhammad Arshad (Arabian Journal of Geosciences, 2021)

Correction to: The trade-off between economic growth and environmental quality: does economic freedom asymmetric matter for Pakistan? - Muhammad Tariq Majeed; Zhiyuan Yu; Adnan Maqbool; Mesfin G. Genie; Sana Ullah; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

The trade-off between economic growth and environmental quality: does economic freedom asymmetric matter for Pakistan? - Muhammad Tariq Majeed; Zhiyuan Yu; Adnan Maqbool; Mesfin Genie; Sana Ullah; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

Occupational health impacts of transport industry: collagen degrader, blood lead, and respiratory illnesses - Waheed Anjum; Nadia Riaz; Muhammad Saqib; Malik Tahir Hayat; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

Use of multivariate adaptive regression splines for prediction of body weight from body measurements in Marecha (Camelus dromedaries) camels in Pakistan - Cem Tırınk; Ecevit Eyduran; Asim Faraz; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq; Irfan Shahzad Sheikh (Tropical Animal Health and Production, 2021)

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

Green logistics, economic growth, and environmental quality: evidence from one belt and road initiative economies - Xiaolong Li; Sidra Sohail; Muhammad Tariq Majeed; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

Does the adaptation of climate-smart agricultural practices increase farmers’ resilience to climate change? - Ihsan Jamil; Wen Jun; Bushra Mughal; Muhammad Haseeb Raza; Muhammad Ali Imran; Ali Waheed (Environmental Science and Pollution Research, 2021)

Prediction of live body weight based on body measurements in Thalli sheep under tropical conditions of Pakistan using CART and MARS - Asim Faraz; Cem Tirink; Ecevit Eyduran; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq (Tropical Animal Health and Production, 2021)

Climate Change Policy Coherence across Policies, Plans, and Strategies in Pakistan—Implications for the China–Pakistan Economic Corridor Plan - Abdul Waheed; Thomas Bernward Fischer; Muhammad Irfan Khan (Environmental Management, 2021)
Climate Change (CC) adaptation and mitigation policy coherence (PC) across sectors is essential to effectively address CC challenges and support synergies. Pakistan is highly vulnerable to CC. In this paper, the extent to which Pakistan’s national and provincial water, agriculture, and energy sector policies, development plans and strategies are aligned in a CC policy coherent manner is established. In this context, a qualitative content document analysis with associated scoring is used to assess government documents. Furthermore, implications of the China–Pakistan Economic Corridor Initiative (CPEC; 2017–2030), the biggest infrastructure investment program ever in Pakistan, are discussed. An important result is that sectoral policies are found to have different degrees of PC. Better coherence is found at federal than at provincial levels. Furthermore, CC policies are found to be more coherently addressed in water and agriculture policies than in energy policies. It is suggested that to achieve higher levels of CC PC, federal and provincial governments should establish mechanisms of intergovernmental consultation for policy-making and cross-sectoral planning, especially in the energy sector. Our findings can help the Government of Pakistan to transform CPEC into a model green Belt and Road Initiative (BRI) in the region. In this context, there are important implications with regards to e.g., reducing coal-based energy projects and environmentally damaging infrastructure activities in sensitive ecosystems. With this paper, the authors want to raise awareness of the key importance of CC PC, particular in context of the BRI. Many countries participating in the initiative have carbon reduction targets in place.

Physical infrastructure, energy consumption, economic growth, and environmental pollution in Pakistan: an asymmetry analysis - Muhammad Afaq Haider Jafri; Huizheng Liu; Muhammad Tariq Majeed; Waheed Ahmad; Sana Ullah; Rui Xue (Environmental Science and Pollution Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Pregnancy status and thyroid function in semi-intensive-kept Marecha she-camels (Camelus dromedarius): managerial implications - Asim Faraz; Carlos Iglesias Pastrana; Annamaria Passantino; Ayman Balla Mustafa; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2020)

Analyzing the association between innovation, economic growth, and environment: divulging the importance of FDI and trade openness in India - Hashim Zameer; Humaira Yasmeen; Muhammad Wasif Zafar; Abdul Waheed; Avik Sinha (Environmental Science and Pollution Research, 2020)

Towards a Web GIS-based approach for mapping a dengue outbreak - Muhammad A. Butt; A. Khalid; A. Ali; S. A. Mahmood; J. Sami; J. Qureshi; K. Waheed; A. Khalid (Applied Geomatics, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Zinc and iron complexes of oleanolic acid, (OA) attenuate allergic airway inflammation in rats - Adnan Jehangir; Muhammad Shahzad; Khadija Shahid; Akbar Waheed; Farhana Ayub (Inflammopharmacology, 2019)

Sewage waste water application improves the productivity of diverse wheat (Triticum aestivum L.) cultivars on a sandy loam soil - Muhammad Ijaz; Abdul Waheed; Sami Ul-Allah; Ahmad Nawaz; Allah Wasaya; Abdul Sattar; Ahmad Sher (Environmental Science and Pollution Research, 2019)

Assessment of heavy metals in different organs of cattle egrets (Bubulcus ibis) from a rural and urban environment in Pakistan - Roheela Yasmeen; Hifsa Ali Muhammad; Syeda Shazia Bokhari; Uzma Rafi; Abdul Shakoor; Aisha Waheed Qurashi (Environmental Science and Pollution Research, 2019)

Biochar for sustainable soil and environment: a comprehensive review - Niaz Muhammad; Mubashir Hussain; Waheed Ullah; Taj Ali Khan; Shafaqat Ali; Ali Akbar; Rukhsanda Aziz; Muhammad Khalid Rafiq; Robert Thomas Bachmann; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Evidence of genetically diverse virulent mating types of Phytophthora capsici from Capsicum annum L. - Kiran Nawaz; Ahmad Ali Shahid; Louis Bengyella; Muhammad Nasir Subhani; Muhammad Ali; Waheed Anwar; Sehrish Iftikhar; Shinawar Waseem Ali (World Journal of Microbiology and Biotechnology, 2018)

Ecotoxicological evaluation of two anti-dandruff hair shampoos using Lemna minor - Azizullah Azizullah; Shakirullah Khan Shakir; Shahana Shoaib; Halima Bangash; Nadia Taimur; Waheed Murad; Muhammad Khan Daud (Environmental Monitoring and Assessment, 2018)

First report of leaf spot caused by Phytophthora capsici on chili pepper (Capsicum frutescens L.) in Pakistan - Kiran Nawaz; Ahmad Ali Shahid; Muhammad Nasir Subhani; Sehrish Iftikhar; Waheed Anwar (Journal of Plant Pathology, 2018)

A novel trifunctional, family GH10 enzyme from Acidothermus cellulolyticus 11B, exhibiting endo-xylanase, arabinofuranosidase and acetyl xylan esterase activities - Saher Shahid; Razia Tajwar; Muhammad Waheed Akhtar (Extremophiles, 2018)

Genes responsible for powdery mildew resistance and improvement in wheat using molecular marker-assisted selection - Liaqat Shah; Shamsur Rehman; Asif Ali; Muhammad Yahya; Muhammad Waheed Riaz; Hongqi Si; Chuanxi Ma; Jie Lu (Journal of Plant Diseases and Protection, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Mix cropping of legume (Vigna Radiata) and non-legume (Zea Mays) crops alleviates water stress as revealed by growth and biochemical parameters - Kalim Ullah Khan; Waheed Murad; Azizullah Azizullah; Hazir Rahman; Muhammad Daud Khan (Acta Physiologiae Plantarum, 2017)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

mRNA secondary structure engineering of Thermobifida fusca endoglucanase (Cel6A) for enhanced expression in Escherichia coli - Imran Ali; Rehana Asghar; Sajjad Ahmed; Muhammad Sajjad; Muhammad Tariq; M. Waheed Akhtar (World Journal of Microbiology and Biotechnology, 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

Directed Evolution of Clostridium phytofermentans Glycoside Hydrolase Family 9 Endoglucanase for Enhanced Specific Activity on Solid Cellulosic Substrate - Sajjad Ahmad; Hui Ma; Muhammad Waheed Akhtar; Yi-Heng Percival Zhang; Xiao-Zhou Zhang (BioEnergy Research, 2014)

Deciphering the role of Burkholderia cenocepacia membrane proteins in antimicrobial properties of chitosan - Muhammad Ibrahim; Zhongyun Tao; Annam Hussain; Yang Chunlan; Mehmoona Ilyas; Abdul Waheed; Fang Yuan; Bin Li; Guan-Lin Xie (Archives of Microbiology, 2014)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Specific post-transcriptional inhibition of mRNA for ligand binding chain of IgE high affinity receptor - Sobia Rana; Ishrat Waheed; Muhammad Imran (Molecular Biology Reports, 2011)

Transfer of radioactivity from soil to vegetation in Rechna Doab, Pakistan - Abdul Jabbar; Muhammad Tufail; Waheed Arshed; Arshed Salem Bhatti; Syed Salman Ahmad; Perveen Akhter; Muhammad Dilband (Isotopes in Environmental and Health Studies, 2010)

Bovine hypodermosis—a global aspect - Murtaz-ul Hassan; Muhammad Nisar Khan; Muhammad Abubakar; Hafiz Muhammad Waheed; Zafar Iqbal; Manzoor Hussain (Tropical Animal Health and Production, 2010)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Evaluation of the Acute Toxicity of Profenofos and Its Effects on the Behavioral Pattern of Fingerling Common Carp (Cyprinus carpio L., 1758) - Muhammad Ismail; Rahat Ali; Tayyaba Ali; Usman Waheed; Qaiser Mahmood Khan (Bulletin of Environmental Contamination and Toxicology, 2009)

Production and characterization of a highly active cellobiase from Aspergillus niger grown in solid state fermentation - Muhammad Ibrahim Rajoka; Muhammad Waheed Akhtar; Atif Hanif; A. M. Khalid (World Journal of Microbiology and Biotechnology, 2006)